2022
DOI: 10.1039/d2fo00072e
|View full text |Cite
|
Sign up to set email alerts
|

Leafy vegetables fortification enhanced the nutritional profile and reduced the glycemic index of yellow cassava pasta

Abstract: Food-to-food fortification of yellow cassava flour with leafy vegetable powders (Amaranthus and Telfairia occidentalis) was employed in this study to develop cassava-vegetable spaghetti-like pasta products (YP, YPA5, YPA10, YPU5, YPU10,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…As observed for TAC, the whole meal flours showed values of ash content more than twice with respect to cassava. The low TAC level, protein, and TDF content of cassava flour suggests the opportunity to obtain enrichment with other raw materials to obtain products with satisfying nutritional potential, as indicated by Lawal et al [22,26], who found a significant increase in TAC, proteins, and fiber values in cassava flours when enriched with amaranth and pumpkin.…”
Section: Chemical Characterization and Total Antioxidant Capacity Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As observed for TAC, the whole meal flours showed values of ash content more than twice with respect to cassava. The low TAC level, protein, and TDF content of cassava flour suggests the opportunity to obtain enrichment with other raw materials to obtain products with satisfying nutritional potential, as indicated by Lawal et al [22,26], who found a significant increase in TAC, proteins, and fiber values in cassava flours when enriched with amaranth and pumpkin.…”
Section: Chemical Characterization and Total Antioxidant Capacity Of ...mentioning
confidence: 99%
“…Indeed, pasta has been the object of many supplementation strategies to improve its nutritional and health potential [20]. Different attempts to produce sorghum and cassava pasta were conducted providing high value-added ingredients by improving nutritional, technological, and functional properties [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Cassava-vegetable pasta using leafy vegetables namely amaranth leaves and fluted pumpkin leaf (at conc. 5, 10%) was prepared by Lawal et al (163). It was observed that nutritional content improved with the addition of leafy vegetables than control.…”
Section: Extruded Productsmentioning
confidence: 99%
“…The consumer appeal of cassava pasta with pumpkin leaf powder was negatively affected as it was less acceptable compared to the yellow pasta (control).Substantially higher content of protein, fibre, ash, beta-carotene, iron and zinc was reported. [198] Brassica rapa L. ssp. Pekinensis (Chinese cabbage) outer leaf powder…”
Section: Incorporation Of Indigenous Leafy Vegetables As Functional I...mentioning
confidence: 99%